Compact Models for Integrated Circuit Design Conventional Transistors and Beyond - Saha, Samar K. (Taylor & Francis, 2015)
This modern treatise on compact models for circuit computer-aided design (CAD) presents industry standard models for bipolar-junction transistors (BJTs), metal-oxide-semiconductor (MOS) field-effect-transistors (FETs), FinFETs, and tunnel field-effect transistors (TFETs), along with statistical MOS models. Featuring exercise problems at the end of each chapter and extensive references at the end of the book, the text supplies fundamental and practical knowledge necessary for efficient integrated circuit (IC) design using nanoscale devices. It ensures even those unfamiliar with semiconductor physics gain a solid grasp of compact modeling concepts.